The Effect of Mageburan Tradition-Based Learning on Students’ Social Interaction and Collaboration Skills - Komang Surya Adnyana; I Wayan Widiana; Gusti Ngurah Arya Yudaparmita (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2026)
Students’ social interaction and collaboration skills have not yet developed optimally because classroom instruction often provides limited opportunities for meaningful communication, shared responsibility, and collective problem-solving. This condition highlights the need for culturally relevant learning that actively engages students in social and collaborative experiences. Therefore, this study examined the effect of Mageburan tradition-based learning on students’ social interaction and collaboration skills. This study employed a quasi-experimental design using a pretest–posttest control group design involving elementary school students who were assigned to an experimental group receiving Mageburan tradition-based learning and a control group receiving conventional instruction. Data on students’ social interaction and collaboration skills were collected using validated questionnaires and classroom observation sheets. The data were analyzed using descriptive statistics, paired-samples t-tests, independent-samples t-tests, and effect size analysis. The results showed that students who participated in Mageburan tradition-based learning demonstrated significantly greater improvements in social interaction and collaboration skills than those in the control group. Students in the experimental group exhibited better communication, mutual respect, cooperation, shared responsibility, and problem-solving skills during collaborative learning activities. These findings indicate that integrating the Mageburan tradition into social studies instruction not only contributes to the preservation of local cultural heritage but also strengthens students’ social competencies.